Convex projective structures on nonhyperbolic three-manifolds - Ballas, Samuel A.; Danciger, Jeffrey; Lee, Gye-Seon (Geometry & topology, 2018)
Y. Benoist proved that if a closed three-manifold M admits an indecomposable convex real projective structure, then M is topologically the union along tori and Klein bottles of finitely many sub-manifolds each of which admits a complete finite volume hyperbolic structure on its interior. We describe some initial results in the direction of a potential converse to Benoist's theorem.